2019
DOI: 10.1049/el.2019.0660
|View full text |Cite
|
Sign up to set email alerts
|

Landmark‐free clothes recognition with a two‐branch feature selective network

Abstract: In this Letter, the authors present a 'landmark-free' clothes recognition approach. Recent studies have shown that the use of landmark information has achieved great success in the task of clothes recognition. However, the landmark annotation is very labour intensive and time consuming. It also suffers from inter-and intra-individual variability. To overcome these problems, the authors propose a two-branch feature selective network for category classification and attribute prediction. Note that, in this Letter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…erefore, the current English evaluation model often adopts the fixed input characteristics, proposes a cluster analysis method of specific data information, and collects audio input information in real time. In order to improve the efficiency of English text evaluation, scholars put forward an innovative evaluation method based on neural network algorithm and relevant theories [9]. In addition, according to the analysis of English characteristics, they proposed that attention should be paid to the development and construction of English text analysis system based on the limiting factors, and the management and importance of data information in the process of English feature scoring was realized.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the current English evaluation model often adopts the fixed input characteristics, proposes a cluster analysis method of specific data information, and collects audio input information in real time. In order to improve the efficiency of English text evaluation, scholars put forward an innovative evaluation method based on neural network algorithm and relevant theories [9]. In addition, according to the analysis of English characteristics, they proposed that attention should be paid to the development and construction of English text analysis system based on the limiting factors, and the management and importance of data information in the process of English feature scoring was realized.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al used stack self-coding network for speech feature coding and compressed the data to a preset length with minimum reconstruction error [10]. Bibi et al have explored various DL (deep learning) frameworks in speech emotion tasks, and their experiments have demonstrated that feedforward and RNN (recurrent neural network) structures and their variants can be used to assist speech recognition, especially emotion recognition [11].…”
Section: Mnfr-related Research Nazemi Et Al Comprehensivelymentioning
confidence: 99%
“…Lee et al [8] proposed a landmark-free clothes classification via exploiting feature selective network based on VGG-16. A multitask learning network is divided into attribute prediction and category classification.…”
Section: Landmark-free Approachesmentioning
confidence: 99%
“…For category classification and attribute prediction, we applied top-k classification accuracy and top-k recall rate, respectively. We compared the performance with ten recently reported works [4,5,7,8,14,27,30,31,42,43] in fashion analysis. As shown in the Table 2, our model slightly outperforms state-of-the-art approaches using supervised learning in fashion clothing classification.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation